Elevated Serum Levels of the Antiapoptotic Protein Decoy-Receptor 3 Are Associated with Advanced Liver Disease - Giorgos Bamias; Michalis Gizis; Ioanna Delladetsima; Eyfrosyni Laoudi; Spyros I. Siakavellas; Ioannis Koutsounas; Garyfallia Kaltsa; John Vlachogiannakos; Irene Vafiadis-Zouboulis; George L. Daikos; George V. Papatheodoridis; Spiros D. Ladas (Canadian Journal of Gastroenterology and Hepatology)
Background. Decoy-receptor 3 (DcR3) exerts antiapoptotic and immunomodulatory function and is overexpressed in neoplastic and inflammatory conditions. Serum DcR3 (sDcR3) levels during the chronic hepatitis/cirrhosis/hepatocellular carcinoma (HCC) sequence have not been explored. Objective. To assess the levels and significance of sDcR3 protein in various stages of chronic liver disease. Methods. We compared sDcR3 levels between healthy controls and patients with chronic viral hepatitis (CVH), decompensated cirrhosis (DC), and HCC. Correlations between sDcR3 levels and various patient- and disease-related factors were analyzed. Results. sDcR3 levels were significantly higher in patients with CVH than in controls (P<0.01). sDcR3 levels were elevated in DC and HCC, being significantly higher compared not only to controls (P<0.001 for both) but to CVH patients as well (P<0.001 for both). In addition, DcR3 protein was detected in large quantities in the ascitic fluid of cirrhotics. In patients with CVH, sDcR3 significantly correlated to fibrosis severity, as estimated by Ishak score (P=0.019) or by liver stiffness measured with elastography (Spearman r=0.698, P<0.001). In cirrhotic patients, significant positive correlations were observed between sDcR3 levels and markers of severity of hepatic impairment, including MELD score (r=0.653, P<0.001). Conclusions. Circulating levels of DcR3 are elevated during chronic liver disease and correlate with severity of liver damage. sDcR3 may serve as marker for liver fibrosis severity and progression to end-stage liver disease.